2020
DOI: 10.6001/chemija.v31i3.4290
|View full text |Cite
|
Sign up to set email alerts
|

Lithuanian Royal jelly: quality assessment, biological activity and quantitative determination of trans-10-hydroxy-2-decenoic acid in various solvents

Abstract: Royal jelly is a bee product with a high commercial interest due to its exceptional biological properties and unique composition. In this study, we evaluated the quality of Lithuanian Royal jelly, including the water content, antioxidant activity, amount of polyphenolic compounds and pH. The results indicated that Lithuanian Royal jelly had the values of pH, water content as well as polyphenols that were comparable to the data already published. In the study, we also evaluated the impact of various solvents on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
2
1
Order By: Relevance
“…In agreement with those reports, the pH values of the analysed RJ samples were found to be 3.45‐3.80 [31,40] . But the pH values obtained in this study were a little lower than the results of Flanjak et al.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with those reports, the pH values of the analysed RJ samples were found to be 3.45‐3.80 [31,40] . But the pH values obtained in this study were a little lower than the results of Flanjak et al.…”
Section: Resultssupporting
confidence: 91%
“…In agreement with those reports, the pH values of the analysed RJ samples were found to be 3.45-3.80. [31,40] But the pH values obtained in this study were a little lower than the results of Flanjak et al ( 2019) and Kolayli et al (2016), who found pH values between 3.98 and 4.21 and between 3.60 and 5.10, respectively. [33,41] According to the literature, having small differences or close values was completely normal when comparing the current data because the pH value of RJ depends on the acidic substances in its composition, such as fatty acids, phenolic acids, organic acids, and proteins.…”
Section: Resultscontrasting
confidence: 69%
“…Based on the solubility results of RJ and in order to create the biological conditions in the release studies, phosphate buffer saline was used as the acceptor medium [16]. Each experiment was carried out in triplicate.…”
Section: Physical Characterization Of Microemulsionsmentioning
confidence: 99%
“…where ABS s is the absorbance of cells treated with test formulations and ABS control is the absorbance of control cells. Cytotoxicity was expressed as the percentage of cells alive [16].…”
Section: Sirc Cell Viability By Mtt Assaymentioning
confidence: 99%